2022
DOI: 10.1097/aln.0000000000004327
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Neurofilament Light Plasma Concentrations and Cognition before and after Cardiac Surgery: A Prospective Nested Cohort Study

Abstract: Background Neurofilament light is a marker of neuronal injury and can be measured in blood. Postoperative increases in neurofilament light have been associated with delirium after noncardiac surgery. However, few studies have examined the association of neurofilament light changes with postdischarge cognition in cardiac surgery patients, who are at highest risk for neuronal injury and cognitive decline. The authors hypothesized that increased neurofilament light (both baseline and change) wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…We read with interest the recent contribution to your journal from Brown et al , who report an association between a postoperative increase in neurofilament light and worse cognitive outcomes at 1 yr after cardiac surgery. 1 These results build on previous work which has shown that a postoperative increase in neurofilament light is similarly associated with an increased risk of delirium, 2 and we congratulate the authors on their publication.…”
Section: To the Editorsupporting
confidence: 78%
“…We read with interest the recent contribution to your journal from Brown et al , who report an association between a postoperative increase in neurofilament light and worse cognitive outcomes at 1 yr after cardiac surgery. 1 These results build on previous work which has shown that a postoperative increase in neurofilament light is similarly associated with an increased risk of delirium, 2 and we congratulate the authors on their publication.…”
Section: To the Editorsupporting
confidence: 78%
“…The test battery consisted of: the Rey Auditory Verbal Learning Test, 20 Rey Complex Figure Test, 21 Controlled Oral Word Association Test, 22 Symbol Digits Modalities Test, 23 Trail Making Test, 24 and Grooved Pegboard 25 . A composite cognitive z‐score was generated from these scores, consistent with prior work 26 . To obtain this z‐score, individual cognitive test z‐scores at each timepoint were first calculated based on the mean and standard deviation of baseline tests of all patients in the parent study enrolled after delirium testing started.…”
Section: Methodsmentioning
confidence: 99%
“…25 A composite cognitive z-score was generated from these scores, consistent with prior work. 26 To obtain this z-score, individual cognitive test z-scores at each timepoint were first calculated based on the mean and standard deviation of baseline tests of all patients in the parent study enrolled after delirium testing started. Second, timed tests were multiplied by −1 so that higher scores represented better performance.…”
Section: Delirium Assessmentmentioning
confidence: 99%
“…Of the most common, elevated neurofilament light chain has been detected in patients with postoperative delirium 47,48 with higher levels associated with lower baseline cognitive scores before cardiac surgery and increased cognitive decline. 95 Recent studies have detected increased systemic tau protein levels in patients who developed delirium after major cardiac surgery and orthopedic surgery. [54][55][56]96 Mechanistically, overexpression of neuronal tau in a mouse model has been associated with changes in the microvasculature that may affect the integrity of the blood-brain barrier during systemic inflammation, 97 suggesting a possible interplay between elevated circulating tau levels as a conduit for driving breakdown of the blood-brain barrier and promoting further neuroinflammation.…”
Section: Anesthesia and Analgesiamentioning
confidence: 99%